DMSO Effect on Phase Transitions and Vitrification in Cord Blood Erythrocyte Suspension Under 0Â°C - Zinchenko, A. V.; Bobrova, E. N.; Schetinskiy, M. I. (Problems of Cryobiology and Cryomedicine, 2006)
Using the DSC method there were investigated the cord blood erythromass, mixed in 1:1 ratio with DMSO aqueous solutions of different concentrations, as well as the samples of dense sediment and supernatant fluid, obtained after these mixturesâ€™ centrifugation. The temperatures of vitrification, devitrification, crystallisation and melting of eutectic compositions and the temperature of complete melting of systems were determined. There was built a part of diagram for physical states of water-DMSO binary system within the concentration range from 0 up to 60 % (w/w) of DMSO. Using the NMR method it was shown, that the DMSO concentration in supernatant fluid was higher, than in a dense suspension of erythrocytes. This explains the differences in eutectics crystallisation in the samples of erythrocyte dense suspension and in supernatant fluid.